HMGB1 Inhibits Apoptosis Following MI and Induces Autophagy via mTORC1 Inhibition. Issue 5 (21st September 2016) - Foglio, Eleonora; Puddighinu, Giovanni; Germani, Antonia; Russo, Matteo A.; Limana, Federica
Abstract : Exogenous High Mobility Group Box‐1 protein (HMGB1) has been reported to protect the infarcted heart but the underlying mechanism is quite complex. In particular, its effect on ischemic cardiomyocytes has been poorly investigated. Aim of the present study was to verify whether and how autophagy and apoptosis were involved in HMGB1‐induced heart repair following myocardial infarction (MI). HMGB1 (200 ng) or denatured HMGB1 were injected in the peri‐infarcted region of mouse hearts following acute MI. Three days after treatment, an upregulation of autophagy was detected in infarcted HMGB1 treated hearts compared to controls. Specifically, HMGB1 induced autophagy by significantly upregulating the protein expression of LC3, Beclin‐1, and Atg7 in the border zone. To gain further insights into the molecular mechanism of HMGB1‐mediated autophagy, WB analysis were performed in cardiomyocytes isolated from 3 days infarcted hearts in the presence and in the absence of HMGB1 treatment. Results showed that upregulation of autophagy by HMGB1 treatment was potentially related to activation of AMP‐activated protein kinase (AMPK) and inhibition of the mammalian target of rapamycin complex 1 (mTORC1). Accordingly, in these hearts, phospho‐Akt signaling pathway was inhibited. The induction of autophagy was accompanied by reduced cardiomyocyte apoptotic rate and decreased expression levels of Bax/Bcl‐2 and active caspase‐3 in the border zone of 3 days infarcted mice following HMGB1 treatment. We report the first in vivo evidence that HMGB1 treatment in a murine model of acute MI might induce cardiomyocyte survival through attenuation of apoptosis and AMP‐activated protein kinase‐dependent autophagy. J. Cell. Physiol. 232: 1135–1143, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Exogenous High Mobility Group Box‐1 protein (HMGB1) has been reported to protect the infarcted heart but the underlying mechanism is quite complex; in particular, its effect on ischemic cardiomyocytes has been poorly investigated. HMGB1 (200 ng) or denatured HMGB1 were injected in the peri‐infarcted region of mouse hearts following acute MI. We report the first in vivo evidence that HMGB1 treatment in a murine model of acute MI might induce cardiomyocyte survival through attenuation of apoptosis and AMP‐activated protein kinase‐dependent autophagy.